Evaluation of a DNA Aβ42 vaccine in adult rhesus monkeys (Macaca mulatta): antibody kinetics and immune profile after intradermal immunization with full-length DNA Aβ42 trimer - Doris Lambracht-Washington; Min Fu; Pat Frost; Roger N. Rosenberg (Alzheimer’s Research & Therapy, 2017)
Abstract Background Aggregated amyloid-β peptide 1–42 (Aβ42), derived from the cellular amyloid precursor protein, is one of the pathological hallmarks of Alzheimer’s disease (AD). Although active immunization against Aβ42 peptide was successful in AD mouse models and led to removal of plaques and improved memory, a similar clinical trial in humans (Aβ42 peptide immunization with QS-21 adjuvant) was stopped in phase II, when 6% of the treated patients developed encephalitis. Currently ongoing passive immunizations with the injection of preformed monoclonal antibodies against different epitopes within the Aβ1–42 peptide, which do not lead to activation of the immune system, have shown some effects in slowing AD pathology. Active DNA Aβ42 immunizations administered with the gene gun into the skin are noninflammatory because they activate a different T-cell population (Th2) with different cytokine responses eliciting a different humoral immune response. We present our findings in rhesus macaques that underwent the DNA Aβ42 immunization via gene gun delivery into the skin. Methods Six rhesus monkeys received two different doses of a DNA Aβ42 trimer vaccine. The humoral immune response was analyzed from blood throughout the study, and cellular immune responses were determined in peripheral blood mononuclear cells (PBMCs) after three and six immunizations. Results DNA Aβ42 trimer immunization led to high titer antibody responses in the nonhuman primate (NHP) model. Antibodies generated in the rhesus monkeys following DNA Aβ42 immunization detected amyloid plaques consisting of human Aβ42 peptide in the brain of the triple-transgenic AD mouse model. T-cell responses showed no interferon (IFN)-γ- and interleukin (IL)-17-producing cells from PBMCs in Enzyme-Linked ImmunoSpot assays after three immunization time points. At six immunization time points, IFN-γ- and IL-17-producing cells were found in immunized animals as well as in control animals and were thus considered nonspecific and not due to the immunization regimen. IFN-γ and IL-17 secretion in response to Aβ42 peptide restimulation became undetectable after a 3-month rest period. Conclusions Intradermal DNA Aβ42 immunization delivered with the gene gun produces a high antibody response in NHPs and is highly likely to be effective and safe in a clinical AD prevention trial in patients.